2013
DOI: 10.1155/2013/579346
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcerogenic Activity of the Hydroalcoholic Extract of Leaves ofCroton campestrisA. St.-Hill in Rodents

Abstract: Croton campestris A. St.-Hill., popularly known as “velame do campo,” is a species native to the savannah area of Northeast Brazil, which is used by traditional communities in folk medicine for variety of health problems, especially detoxification, inflammation, and gastritis. The hydroalcoholic extract of C. campestris leaves (HELCC) was assessed for its antiulcerogenic effect in gastric lesion models and effect on intestinal motility in mice, and possible mechanisms of action were examined. HELCC showed sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…They are rich in phenolic groups and are chemically classified into hydrolysable and condensed (Paes, Diniz, Marinho, & Lima, 2006). Studies on the pharmacological properties of tannins suggest a significant antibacterial action (Loguercio, Battistin, Vargas, Henzel, & Witt, 2005;Oliveira et al, 2006), as well as anti-inflammatory (Norata et al, 2007), antiparasitic (Morais-Braga et al, 2013) and gastroprotective (Júnior et al, 2013;Pellizzon et al, 2012) activities.…”
Section: Chemical Analysismentioning
confidence: 99%
“…They are rich in phenolic groups and are chemically classified into hydrolysable and condensed (Paes, Diniz, Marinho, & Lima, 2006). Studies on the pharmacological properties of tannins suggest a significant antibacterial action (Loguercio, Battistin, Vargas, Henzel, & Witt, 2005;Oliveira et al, 2006), as well as anti-inflammatory (Norata et al, 2007), antiparasitic (Morais-Braga et al, 2013) and gastroprotective (Júnior et al, 2013;Pellizzon et al, 2012) activities.…”
Section: Chemical Analysismentioning
confidence: 99%
“…Substantial evidence from the literature indicates that Croton campestris A. St.-Hill displays antibacterial [14,15], antibiotic [15,17], molluscicidal [18], and antiinflammatory properties [19]. Recently, our research group reported the antiulcerogenic activity of the leaf extracts of Croton campestris A. St.-Hill [16]. However, the possible mechanism by which Croton campestris A. St.-Hill exerts this action was not clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Croton is composed of 700 species and is distributed in tropical regions. It is popularly known as "velame do campo" and is used through infusions of leaves and roots of the plant in alcoholic beverages and teas and is used in Brazilian folk medicine for gastric, hematological, and inflammatory disorders, as well as respiratory problems [14][15][16]. Substantial evidence from the literature indicates that Croton campestris A. St.-Hill displays antibacterial [14,15], antibiotic [15,17], molluscicidal [18], and antiinflammatory properties [19].…”
Section: Introductionmentioning
confidence: 99%
“…(bom-nome; Mota et al, 2008), Croton campestris A. St.-Hill (Júnior et al, 2013), Croton urucurana Baillon bark (urucuana) (Cordeiro et al, 2012), Campomanesia xanthocarpa O. Berg (gabiroba; Markman et al, 2004).…”
Section: Introductionunclassified